Impact of sociodemographic characteristics, nutritional status and perceived stress in body weight concern of female college students - Dias, Juliana Chioda Ribeiro (2017)
Aim: to estimate the contribution of nutritional status, perceived stress and sociodemographic variables in college students’ body weight concern. Method: participated 850 Brazilian students of one public university. Information such as age, area of study and schedule of the undergraduate course, body weight and height, economic status, household’s education level, household, studies funding and medication intake due to studies and labour activity were collected. Perceived stress and body weight concern were assessed, respectively, with the Portuguese versions of the Perceived Stress Scale (PSS) and the Weight Concerns Scale (WCS). The impact of several variables on body weight concern was verified by a causal model developed using Structural Equation Modelling. The goodness-of-fit of the model was evaluated using chi-square ratio index and degrees of freedom (c2/df), Comparative Fit Index (CFI), Normed of Fit Index (NFI), and Root Mean Square Error of Approximation (RMSEA). The contribution (β) and significance of causal pathways were evaluated using the z-test critical ratios (p < .05). Results: a significant contribution of the variables perceived stress, economic status and nutritional status in college students’ body weight concern was verified. The fit of the final model was adequate (c²/df = 4.38; CFI = .91; GFI = .93; RMSEA = .06) and explained 19% of the variability in body weight concern with a positive impact of nutritional status, perceived stress and economic status. Conclusion: the results should serve as an alert to researchers in this area of study and health professionals, highlighting the importance of performing the diagnosis of such manifestations and/or propose prevention strategies.